Tuesday

September 16, 2014

September 16, 2014

Posted by **Hannah** on Monday, February 27, 2012 at 12:07pm.

- AB Calculus -
**Steve**, Monday, February 27, 2012 at 2:09pmplug in y to see whether it satisfies the differential equation

y = e^(-x)

y' = -e^(-x)

3y' + 4y = -3e^(-x) + 4e^(-x) = e^-x

so, it does satisfy it.

- AB Calculus -
**Kris**, Tuesday, February 28, 2012 at 9:21pmOh, okay. I get it now. Thanks!

**Answer this Question**

**Related Questions**

calculus - verify that y=c/x^2 is a general solution of the differential ...

calculus-differential equation - Consider the differential equation: (du/dt)=-u^...

Calculus - Which of the following is a separable, first-order differential ...

calculus differential equation - Find in implicit form the general solution of ...

calculus differential equation - Find in implicit form the general solution of ...

calculus - verify that y=C1e^2x + C2e^-3 is a solution of the differential ...

calculus - consider the differential equation dy/dx= (y - 1)/ x squared where x ...

Differential Equations - Consider the differential equation: dy/dt=y/t^2 a) Show...

Differential Equations - Consider the differential equation: dy/dt=y/t^2 a) Show...

Differential Equations - The velocity v of a freefalling skydiver is well ...